Rehabilitation of tropical rainforests based on indigenous species for degraded areas in Sarawak, Malaysia - Azani, A.M.; Majid, N.M.; Meguro, S. (Center for International Forestry Research, 2001)
A study was conducted on forest rehabilitation based on indigenous species at the Universiti Putra Malaysia, Bintulu, Sarawak. Areas of open abandoned shifting cultivation, man-made mounds, Macaranga secondary forest and shrubby undergrowth were used for trial planting with different types of planting techniques. The research showed that selected species from the natural vegetation community easily adapt to the site conditions similar to their native habitat. The planted seedlings were classified as light demanding, shade tolerant and late growth species on the basis of their height growth performance in the trials. The indigenous tree species recommended for checkerboard plantations are: Shorea ovata, S. mecistopteryx, S. macrophylla, Dryobalanops aromatica, Parashorea parvifolia, Hopea beccariana, Durio carinatus and Eusideroxylon zwageri.